Copper paste
By using suitable alcohol solvents and copper powder in copper pastes, the viscosity and oxidation resistance are optimized, and the problem that existing copper pastes are difficult to achieve chip shear strength during low temperature and short-term pressurized sintering is solved, achieving high efficiency Sintered body formation and excellent thermal conductivity and bonding strength.
Patent Information
- Application Number
- CN202380050209.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-10
- Filing Date
- 2023-08-10
- Publication Date
- 2025-02-14
AI Technical Summary
When existing copper pastes are pressurized and sintered for a short time at low temperature, it is difficult to achieve the desired chip shear strength, and the fine refinement of particles can easily lead to pores, protrusions or cracks, affecting the bonding strength.
A copper paste containing copper powder and an alcohol solvent is used, which consists of a first alcohol and a second alcohol with moderate viscosity. The ratio and type of the first alcohol and the second alcohol are designed to optimize the viscosity and oxidation resistance, thereby forming excellent sintering. Copper paste with shear strength of the body chip.
The copper paste has achieved good oxidation resistance and high chip shear strength, avoiding defects caused by particle microrefining, and ensuring excellent thermal conductivity and bonding strength.
Smart Images

Figure CN119452433A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a copper paste. Background Art
[0002] The power module is composed of semiconductor elements that control power, insulating heat dissipation substrates, and cooling fins. Among them, as semiconductor elements, materials such as Si, SiC, GaN, and Ga2O3 can be used. In addition, as insulating heat dissipation substrates, ceramic materials with excellent thermal conductivity such as Al2O3, AlN, and Si3N4 can be used. Furthermore, Al can be used as a heat sink. In order to join the various components, a metal film such as Cu, Ni, and Ag is formed on the surface where the semiconductor element is joined, and a Cu thin plate called Direct Bonding of Copper (DBC) or Active Metal Brazing (AMB) is formed on the surface where the insulating heat dissipation substrate is joined. Sometimes an Ag thin film can also be formed on the surface of the Cu thin plate.
[0003] The bonding of a semiconductor element to an insulating heat dissipation substrate is generally referred to as "chip bonding". This chip bonding is formed by the following method: sequentially performing a process of applying a conductive paste on the surface of a Cu thin plate formed on an insulating heat dissipation substrate by screen printing or dispensing (coating process), a process of drying the paste (drying process), a process of arranging a semiconductor element at the portion where the conductive paste is applied (chip mounting process), a process of heating the conductive paste in a state where a stress of about 20 MPa is applied in the stacking direction of the obtained stack (pressure sintering process), and forming a metal thin film as a sintered body of the conductive paste on the surface of the semiconductor element and bonding. Typical sintering conditions are 3-10 minutes at a temperature of 250-300°C, and the atmosphere can be air, nitrogen, hydrogen, etc. depending on the paste used. The bonding strength of the chip bonding formed in this way is required to be at least 30 MPa as a chip shear strength.
[0004] Here, since the sintered body formed by the conductive paste has excellent thermal conductivity, the heat generated when the semiconductor element operates at high voltage and high current can be effectively transferred to the insulating heat dissipation substrate, and the heat can be dissipated from the cooling fin. As such a paste for chip bonding, a high-concentration lead-containing solder paste has been used in the past, but in order to cope with the higher operating temperature of the element, it has been replaced by a silver paste with better thermal conductivity, and in recent years, copper paste that can achieve low cost has attracted attention.
[0005] However, when the copper paste is pressure-sintered under the above sintering conditions, it is not possible to fully sinter due to the low temperature and short time compared to the usual sintering conditions, and it is difficult to obtain the chip shear strength required as a product. Therefore, in order to promote sintering, a solution has been proposed to prepare the paste using fine copper particles with a large surface area.
[0006] For example, in Non-Patent Document 1, it is proposed to use copper nanoparticles having an average particle size of 50-60 nm, which are obtained by reducing a mixed solution of copper hydroxide and disodium nitrilotriacetate with hydrazine, in a copper paste. It is reported that this copper paste is formed into a sintered body by heating at a low temperature of 200° C. for 30 minutes in a nitrogen atmosphere, and the maximum die shear strength of die bonding is 39 MPa.
[0007] Prior art documents
[0008] Non-patent documents
[0009] Non-patent document 1: Y. Kamikoriyama, H. Imamura, A. Muramatsu, K. Kanie, Sci. Rep., 9, 899 (2019). Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, if the particles are miniaturized as in Non-Patent Document 1, the particles aggregate, and holes or protrusions are easily formed after the coating and drying process, or cracks are easily formed. These defects will continue to exist as defects of the joint body after the pressure sintering process, which will cause the chip shear strength to decrease. In addition, if the particles are miniaturized, the specific surface area becomes larger, and the particle surface is oxidized during the storage of the copper particles or in the drying process after the copper paste is applied, the sintering property is deteriorated, and the chip shear strength is deteriorated, and the thermal conductivity required for heat dissipation is reduced.
[0012] The present invention has been made in view of the above-mentioned actual circumstances, and an object of the present invention is to provide a copper paste having good oxidation resistance and excellent die shear strength of a sintered body formed therefrom.
[0013] Means of solving problems
[0014] The inventors of the present invention have conducted intensive research to solve the above-mentioned problems. As a result, it was found that the following copper paste has good oxidation resistance and the chip shear strength of the sintered body formed is excellent, thereby completing the present invention. The copper paste comprises copper powder and an alcohol solvent, and the alcohol solvent comprises a first alcohol and a second alcohol. The first alcohol is selected from one or more monohydric alcohols and dihydric alcohols having a viscosity of 3 mPa·s or more and 70 mPa·s or less at 25°C, and the second alcohol is selected from one or more dihydric alcohols and trihydric alcohols having a viscosity of 300 mPa·s or more and 1000 mPa·s or less at 25°C. The copper paste has a high viscosity at 25°C and a shear rate of 10 s -1 Viscosity η 10 is greater than 1Pa·s and less than 50Pa·s, and the square root of the Casson yield stress σ0√σ0 is 10Pa 1 / 2 That is, the present invention provides the following contents.
[0015] (1) A copper paste comprising copper powder and an alcohol solvent, wherein the alcohol solvent comprises a first alcohol and a second alcohol, wherein the first alcohol is selected from one or more monohydric alcohols and dihydric alcohols having a viscosity of 3 mPa·s or more and 70 mPa·s or less at 25°C, and the second alcohol is selected from one or more dihydric alcohols and trihydric alcohols having a viscosity of 300 mPa·s or more and 1000 mPa·s or less at 25°C, and the copper paste has a viscosity of 100 mPa·s or more and a shear rate of 10 s -1 Viscosity η 10 is greater than 1Pa·s and less than 50Pa·s, and the square root of the Casson yield stress σ0√σ0 is 10Pa 1 / 2 the following.
[0016] (2) The copper paste according to (1), wherein the Casson viscosity η ∞ The square root of √η ∞ 1 (Pa·s) 1 / 2 the following.
[0017] (3) The copper paste according to (1) or (2), wherein the copper powder comprises first copper particles, second copper particles and third copper particles, the first copper particles have an average particle size of 50 nm to 900 nm, the second copper particles have an average particle size of 150 nm to 1 μm, and the average particle size is greater than that of the first copper particles by 100 nm or more, and the third copper particles are plate-shaped, scaly, flat or flake-shaped and have an average particle size of 1.5 μm to 20 μm.
[0018] (4) The copper paste according to (3), wherein the copper powder contains 1 mass % to 30 mass % of the second copper particles and 5 mass % to 60 mass % of the third copper particles relative to 100 mass % of the copper powder.
[0019] (5) The copper paste according to (1) or (2), wherein the total amount of the first alcohol and the second alcohol is 5 mass % or more and 50 mass % or less relative to 100 mass % of the total amount of the copper powder, the first alcohol and the second alcohol.
[0020] (6) The copper paste according to (1) or (2), wherein the copper paste does not contain a resin, or contains more than 0 mass % and 10 mass % or less of the resin relative to 100 mass % of the copper powder.
[0021] (7) The copper paste according to (1) or (2), wherein the copper paste does not contain a silane coupling agent having an epoxy group and a silane coupling agent having an amino group, or contains a total amount of more than 0 mass % and 0.05 mass % or less of the silane coupling agent having an epoxy group and the silane coupling agent having an amino group relative to 100 mass % of the copper powder.
[0022] (8) The copper paste according to (1) or (2), wherein the first alcohol comprises one or more selected from 1-hexanol, 1-heptanol, 2-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, benzyl alcohol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 2,3-butylene glycol.
[0023] (9) The copper paste according to (3), wherein at least one of the first copper particles and the second copper particles is coated with a polysaccharide on at least a portion of a surface.
[0024] (10) The copper paste according to (3), wherein at least one of the first copper particle and the second copper particle contains one or more selected from octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, and tetradecanoic acid on at least a portion of the surface.
[0025] Effects of the Invention
[0026] According to the present invention, a copper paste having good oxidation resistance and having an excellent die shear strength of a sintered body can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is Comparative Example 2 (η 10 Casson curve of paste with a viscosity of 1.5-1.5 Pa·s.
[0028] Figure 2 is Comparative Example 1 (η 10 Casson curve of paste with φ =11 Pa·s).
[0029] Figure 3 Example 4 (η10 Casson curve of paste with φ = 8 Pa·s).
[0030] Figure 4 This is an optical microscope photograph of the dried product of the paste of Comparative Example 1.
[0031] Figure 5 This is an optical microscope photograph of the dried paste of Example 4. DETAILED DESCRIPTION
[0032] Hereinafter, embodiments of the present invention will be described. However, the present invention is not limited to the description of the embodiments and can be implemented with appropriate modifications.
[0033] Copper paste
[0034] The copper paste involved in this embodiment includes copper powder and an alcohol solvent. The alcohol solvent includes a first alcohol and a second alcohol, the first alcohol is selected from one or more monohydric alcohols and dihydric alcohols having a viscosity of 3 mPa·s or more and 70 mPa·s or less at 25°C, the second alcohol is selected from one or more dihydric alcohols and trihydric alcohols having a viscosity of 300 mPa·s or more and 1000 mPa·s or less at 25°C, and the copper paste is molten at 25°C and a shear rate of 10 s -1 Viscosity η 10 is greater than 1Pa·s and less than 50Pa·s, and the square root of the Casson yield stress σ0√σ0 is 10Pa 1 / 2 the following.
[0035] In addition, regarding the viscosity of the first alcohol and the second alcohol, since both alcohols are Newtonian viscous bodies and the viscosity does not depend on the shear rate, it refers to the viscosity at an arbitrary shear rate.
[0036] Since copper paste is a non-Newtonian viscous body, it is measured using a cone-plate type dynamic viscoelasticity measuring device (e.g., RST cone-plate Rheometer manufactured by Brookfield) at a shear rate of 10 s. -1 The viscosity of the copper paste.
[0037] In the copper paste of this embodiment, at least two alcohols are used as the organic solvent of the dispersion medium. Thus, oxidation of the copper powder is suppressed during storage and sintering. The sintered body thus obtained has a reduced amount of oxides present therein and has excellent thermal conductivity and bonding strength.
[0038] In the copper paste according to the present embodiment, the shear rate is 10 s -1 Viscosity η 10 The shear rate is 1 Pa·s or more and 50 Pa·s or less. -1 Viscosity η10 When the viscosity η is set to a value above the required value, the paste can be prevented from penetrating under the printing plate during application by printing. In addition, the paste applied by dispensing can be prevented from flowing and the desired shape can be maintained. 10 When the thickness is below the required value, the paste in the gap between the semiconductor element and the insulating heat dissipating substrate can be evenly distributed in the chip mounting process, the sintering variation of each part of the pressure sintered body can be suppressed, and the chip shear strength variation depending on the part can be suppressed.
[0039] As shear rate 10s -1 Viscosity η 10 , there is no particular limitation as long as it is 1Pa·s or more and 50Pa·s or less, and for example, preferably 1.5Pa·s or more, 2Pa·s or more, 2.5Pa·s or more, 3Pa·s or more, 3.5Pa·s or more, 4Pa·s or more, 4.5Pa·s or more, 5Pa·s or more, 5.5Pa·s or more, 6Pa·s or more, 6.5Pa·s or more, 7Pa·s or more, 7.5Pa·s or more, 8Pa·s or more, 8.5Pa·s or more, 9Pa·s or more, 9.5Pa·s or more, 10Pa·s or more. On the other hand, as a shear rate of 10s -1 Viscosity η 10 , preferably 49 Pa·s or less, 47 Pa·s or less, 45 Pa·s or less, 42 Pa·s or less, 40 Pa·s or less, 37 Pa·s or less, 35 Pa·s or less, 32 Pa·s or less, or 30 Pa·s or less.
[0040] In the copper paste according to the present embodiment, the square root of the Casson yield stress σ0√σ0 is 10 Pa. 1 / 2 The square root √σ0 of the Casson yield stress σ0 is an indicator of the size and cohesive strength of the aggregates. By making √σ0 less than the required value, the aggregates can be prevented from being large or strongly coagulated, thereby preventing the formation of holes or protrusions on the surface of the dried paste and reducing the shear strength of the chip after pressure sintering.
[0041] As the square root of the Casson yield stress σ0√σ0, as long as it is 10Pa 1 / 2 The following is not particularly limited, for example, preferably 9.7 Pa 1 / 2 Below, 9.5Pa 1 / 2 Below, 9.2Pa 1 / 2 Below, 9Pa 1 / 2 Below, 8.7Pa 1 / 2 Below, 8.5Pa 1 / 2 Below, 8.2Pa 1 / 2 Below, 8Pa 1 / 2Below, 7.7Pa 1 / 2 Below, 7.5Pa 1 / 2 Below, 7.2Pa 1 / 2 Below, 7Pa 1 / 2 Below, 6.7Pa 1 / 2 Below, 6.5Pa 1 / 2 Below, 6.2Pa 1 / 2 Below, 6Pa 1 / 2 Below, 5.7Pa 1 / 2 Below, 5.5Pa 1 / 2 Below, 5.2Pa 1 / 2 Below, 5Pa 1 / 2 the following.
[0042] In the copper paste according to the present embodiment, the Casson viscosity η ∞ , is not particularly limited, but is preferably the square root √η ∞ 1 (Pa·s) 1 / 2 Below, 0.97 (Pa·s) 1 / 2 Below, 0.95 (Pa·s) 1 / 2 Below, 0.92 (Pa·s) 1 / 2 Below, 0.9 (Pa·s) 1 / 2 Below, 0.87 (Pa·s) 1 / 2 Below, 0.85 (Pa·s) 1 / 2 Below, 0.82 (Pa·s) 1 / 2 Below, 0.8 (Pa·s) 1 / 2 Below, 0.77 (Pa·s) 1 / 2 Below, 0.75 (Pa·s) 1 / 2 Below, 0.72 (Pa·s) 1 / 2 Below, 0.7 (Pa·s) 1 / 2 Below, 0.67 (Pa·s) 1 / 2 Below, 0.65 (Pa·s) 1 / 2 Below, 0.62 (Pa·s) 1 / 2 Below, 0.6 (Pa·s) 1 / 2 Below, 0.57 (Pa·s) 1 / 2 Below, 0.55 (Pa·s) 1 / 2 Below, 0.52 (Pa·s) 1 / 2 Below, 0.5 (Pa·s) 1 / 2 Below. Casson viscosity η ∞ The square root of √η ∞ It can be used as an index of the ease of paste movement in the paste coating process, by making √η ∞When the value is equal to or less than a required value, the paste can easily follow the movement of the squeegee during screen printing, thereby preventing the occurrence of defects in the paste application area and the occurrence of uneven paste thickness.
[0043] (Determination of dynamic viscoelastic behavior of copper paste)
[0044] The measurement was performed using a dynamic viscoelasticity measuring device equipped with a cone-plate type spindle (e.g., RST cone-plate Rheometer manufactured by Brookfield Corporation) and the shear rate was set to 10 s. -1 The viscosity of the copper paste under 10 In addition, a Casson curve was obtained with the square root (√σ) of the shear stress (σ) as the vertical axis and the square root of the shear rate (γ) as the horizontal axis (√γ). When an approximate straight line is obtained from this curve, the shear rate is 10s -1 The intercept of the approximate straight line in the above region with the vertical axis is the square root of the Casson yield stress (√σ0), and the slope is the square root of the Casson viscosity (√η ∞ ).
[0045] (Alcohol solvent)
[0046] The organic solvent used in the copper paste involved in the present embodiment is an alcohol solvent composed of a monohydric or dihydric alcohol and a dihydric or trihydric alcohol with different viscosities. If a polyhydric alcohol with a valence of 4 or more is used as a solvent, especially when sintering is performed at a low temperature of about 300°C or less and in a reducing atmosphere or a nitrogen atmosphere, the alcohol remains in the sintered body, which will reduce the conductivity and adhesion strength. On the other hand, if only a monohydric alcohol is used as a solvent, it is easy to volatilize during the storage and printing of the copper paste, causing the viscosity of the copper paste to change, which will deteriorate the processability. In the copper paste involved in the present embodiment, by combining a monohydric or dihydric alcohol and a dihydric or trihydric alcohol with different viscosities, such a problem can be avoided, and a copper paste with excellent physical properties and processability in which copper powder is uniformly dispersed can be provided. In particular, since the second alcohol with high viscosity is included, not only can the change from the desired shape caused by the collapse of the paste after coating be suppressed, but also, as described later, the viscosity of the copper paste can be adjusted to an appropriate value even without a binder component such as a resin. If the copper paste does not contain a resin component, there is no need to consider the generation of carbon residues from the resin component, and sintering can be performed at a relatively low temperature in a non-oxidizing atmosphere.
[0047] In this specification, "alcohol solvent" refers to a mixed solvent mainly composed of alcohol, and may also include a small amount of water or an organic solvent other than alcohol, for example, a mixed solvent containing one or more selected from ethers, ketones, esters, etc. in an amount of 1-20 mass%, 2-17 mass%, 3-15 mass%, 4-12 mass%, 5-10 mass%. In addition, hydrocarbon solvents, halogenated hydrocarbon solvents, etc. may also be included, but nitrogen-containing solvents such as amines and amides tend to remain in the dried solid, so they are not included, or even if included, they are preferably 5 mass% or less, 4 mass% or less, 3 mass% or less, 2 mass% or less, 1 mass% or less, 0.7 mass% or less, 0.5 mass% or less, 0.2 mass% or less, or 0.1 mass% or less.
[0048] The total amount of the first alcohol and the second alcohol is not particularly limited, and is preferably 5% by mass or more, 5.5% by mass or more, 6% by mass or more, 6.5% by mass or more, 7% by mass or more, 7.5% by mass or more, or 8% by mass or more relative to the total amount of 100% by mass of the copper paste. On the other hand, the total amount of the first alcohol and the second alcohol is preferably 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, or 20% by mass or less relative to the total amount of 100% by mass of the copper paste. By making the total amount of the first alcohol and the second alcohol more than the required amount, the copper paste can be applied to the entire interface with a uniform layer thickness, so that the bonding strength becomes excellent. In addition, by making the total amount of the first alcohol and the second alcohol less than the required amount, the solvent will not remain during firing, and the reduction of conductivity or bonding strength can be suppressed.
[0049] The total amount of the first alcohol and the second alcohol is not particularly limited, but is preferably 5% by mass or more, 7% by mass or more, 10% by mass or more, 12% by mass or more, 15% by mass or more, 17% by mass or more, 20% by mass or more, 22% by mass or more, 25% by mass or more, 27% by mass or more, or 30% by mass or more, based on 100% by mass of the total amount of the copper powder, the first alcohol, and the second alcohol. On the other hand, the total amount of the first alcohol and the second alcohol is preferably 50% by mass or less, 47% by mass or less, 45% by mass or less, 42% by mass or less, 40% by mass or less, 37% by mass or less, 35% by mass or less, 32% by mass or less, 30% by mass or less, 27% by mass or less, or 25% by mass or less, based on 100% by mass of the total amount of the copper powder, the first alcohol, and the second alcohol.
[0050] The total amount of the first alcohol and the second alcohol is not particularly limited, but is preferably 70% by mass or more, 75% by mass or more, 80% by mass or more, 85% by mass or more, 90% by mass or more, 95% by mass or more, 97% by mass or more, 98% by mass or more, 99% by mass or more, 99.9% by mass or more, or 99.99% by mass or more, relative to 100% by mass of the total solvent in the copper paste. Since alcohols, especially triols, have a reducing effect, by increasing their content in the solvent of the copper paste, oxidation of copper powder can be more effectively suppressed.
[0051] The ratio (X / Y) of the mass (X) of the first alcohol and the mass (Y) of the second alcohol in the copper paste is not particularly limited, but is preferably 0.2 or more, 0.3 or more, 0.4 or more, or 0.5 or more. On the other hand, the ratio (X / Y) of the mass (X) of the first alcohol and the mass (Y) of the second alcohol is preferably 8 or less, 7 or less, 6 or less, or 5 or less. In order to make the bonding strength of the copper paste, such as the chip shear strength between the chip and the substrate, a sufficient value, it is necessary to print the copper paste layer at the interface between the chip and the substrate with a substantially uniform thickness. By making the ratio (X / Y) greater than the required value, a viscosity suitable for coating is obtained, resulting in excellent bonding strength. By making the ratio (X / Y) less than the required value, the sintering property of the sintered body obtained by fully expressing the reducing effect of the alcohol becomes particularly good, and high conductivity and bonding strength can be obtained.
[0052] (1st alcohol)
[0053] The first alcohol is one or more alcohols selected from monohydric alcohols and dihydric alcohols having a viscosity of 3 mPa·s or more and 70 mPa·s or less at 25° C. When the viscosity of the first alcohol is within such a range, the copper paste can be easily applied and good workability can be ensured.
[0054] The boiling point of the first alcohol is not particularly limited, but is preferably 150°C or more, 155°C or more, 160°C or more, 165°C or more, 170°C or more, 175°C or more, 180°C or more, 185°C or more, or 190°C or more. On the other hand, the boiling point of the first alcohol is preferably 250°C or less, 245°C or less, 240°C or less, 235°C or less, 230°C or less, 225°C or less, 220°C or less, 215°C or less, 210°C or less, 205°C or less, or 200°C or less. By making the boiling point of the first alcohol 150°C or more, it is possible to prevent sudden boiling during heating and the formation of voids in the paste, prevent the sintering property from being reduced, and improve the thermal conductivity and bonding strength of the sintered body. In addition, if the boiling point of the first alcohol is 150°C or more, even if the copper paste is stored at room temperature, the solvent will not volatilize and cause viscosity changes in a short period of time. Therefore, it is not necessary to store it by refrigeration or freezing, and the storage cost can be reduced. In addition, in this specification, unless otherwise specified, the "boiling point" means the boiling point under atmospheric pressure.
[0055] The boiling point of the first alcohol is not particularly limited, but is preferably 50° C. or more lower than the firing temperature of the copper paste.
[0056] The vapor pressure of the first alcohol is not particularly limited, but preferably the vapor pressure at room temperature, for example, 25° C. is 0.1 Pa or more, 0.2 Pa or more, 0.3 Pa or more, 0.4 Pa or more, 0.5 Pa or more, 0.6 Pa or more, 0.7 Pa or more, 0.8 Pa or more, 0.9 Pa or more, 1 Pa or more, 1.2 Pa or more, 1.5 Pa or more, 1.7 Pa or more, 2 Pa or more, 2.2 Pa or more, 2.5 Pa or more, 2.7 Pa or more, or 3 Pa or more. On the other hand, the vapor pressure of the first alcohol is not particularly limited, but preferably 100 Pa or less, 90 Pa or less, 80 Pa or less, 70 Pa or less, 60 Pa or less, 50 Pa or less, 40 Pa or less, or 30 Pa or less. By setting the vapor pressure of the first alcohol within a desired range, excellent storage stability and printability can be achieved.
[0057] In specific examples, as the first alcohol, for example, 1-hexanol (viscosity 4.58 mPa·s, boiling point 158°C, vapor pressure 80 Pa), 1-heptanol (viscosity 5.81 mPa·s, boiling point 176°C, vapor pressure 44 Pa), 2-heptanol (viscosity 3.96 mPa·s, boiling point 159°C, vapor pressure 78 Pa), 1-octanol (viscosity 7.29 mPa·s, boiling point 195°C, vapor pressure 24 Pa), 2-octanol (viscosity 6.49 mPa·s, boiling point 180°C, vapor pressure 42 Pa), 2-ethyl-1-hexanol (viscosity 6.27 mPa·s, boiling point 185°C, vapor pressure 35Pa), benzyl alcohol (viscosity 5.47mPa·s, boiling point 205°C, vapor pressure 18Pa) and other monohydric alcohols; ethylene glycol (viscosity 16.1mPa·s, boiling point 197°C, vapor pressure 20Pa), 1,2-propylene glycol (viscosity 40.4mPa·s, boiling point 188°C, vapor pressure 28Pa), 1,3-propylene glycol (viscosity 47mPa·s, boiling point 214°C, vapor pressure 5Pa), 2,3-butanediol (viscosity 45mPa·s, boiling point 182°C, vapor pressure <100Pa) and other dihydric alcohols. Among them, as the first alcohol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, ethylene glycol, and 1,2-propylene glycol are preferably used. As the first alcohol, as long as the above-mentioned necessary conditions for the first alcohol are met, one type may be used alone, or two or more types may be used in combination. In addition, the viscosity and vapor pressure are values at 25° C. As described above, since the first alcohol has a low viscosity, the viscosity of the copper paste can be adjusted to an appropriate value by adding a smaller amount. Therefore, the total amount of organic solvent in the copper paste can be reduced, and the residual organic solvent component during firing can be suppressed.
[0058] (2nd alcohol)
[0059] The second alcohol is one or more alcohols selected from diols and triols having a viscosity of 300 mPa·s or more and 1000 mPa·s or less at 25° C. If the viscosity of the second alcohol is within this range, it is possible to prevent the copper paste from collapsing before sintering and failing to form a desired shape, and the workability of the copper paste is not impaired.
[0060] The boiling point of the second alcohol is not particularly limited, but is preferably 150°C or higher, 160°C or higher, 170°C or higher, 180°C or higher, 190°C or higher, 195°C or higher, 200°C or higher, 205°C or higher, 210°C or higher, 215°C or higher, 220°C or higher, 225°C or higher, 230°C or higher, 235°C or higher, 240°C or higher, 245°C or higher, 250°C or higher, 255°C or higher, 260°C or higher, 265°C or higher, 270°C or higher, 275°C or higher, 280°C or higher, or 285°C or higher. On the other hand, the boiling point of the second alcohol is preferably 320°C or lower, 315°C or lower, 310°C or lower, 305°C or lower, 300°C or lower, or 295°C or lower. By setting the boiling point of the second alcohol within such a range, the second alcohol will not remain in the gaps between the copper particles in the sintered body even after low-temperature sintering, thereby preventing a decrease in thermal conductivity. By making the boiling point of the second alcohol above the desired value, it is possible to prevent sudden boiling during heating and the reduction of sinterability caused by the generation of voids in the paste, and to improve the thermal conductivity and bonding strength of the sintered body. In addition, if the boiling point of the second alcohol is above the desired value, even if the copper paste is kept at room temperature, the solvent will not volatilize and cause viscosity changes in a short period of time. Therefore, it is not necessary to keep it by refrigeration or freezing, and the storage cost can be reduced.
[0061] The boiling point of the second alcohol is not particularly limited, but is preferably at least 50° C. lower than the firing temperature of the copper paste.
[0062] As the second alcohol, an alcohol having a higher boiling point than the first alcohol is preferably used. By including the low-viscosity first alcohol, the copper paste involved in the present embodiment has an appropriate viscosity and excellent workability, but there is no need to adjust the viscosity after the paste is applied. From the viewpoint of preventing the edge collapse of the copper paste, it is preferred that the first alcohol disappears. On the other hand, among alcohols, since diols and triols, especially triols, have a high reducing effect, it is preferred that a second alcohol containing at least any one of them is present at a high concentration during firing. Therefore, as the second alcohol, by using an alcohol having a higher boiling point than the first alcohol and evaporating at a temperature close to the firing temperature of the copper paste, good workability can be maintained, and oxidation of copper powder can be more effectively suppressed.
[0063] In addition, when the vapor pressure at room temperature, for example, 25°C, is 1 mPa or more and 5 Pa or less, and further, the vapor pressure is 1.5 Pa or less, and particularly 1 Pa or less, the storage stability is further improved and the oxidation inhibition effect during calcination is further improved, which is preferred. This effect is particularly significant when the vapor pressure of the second alcohol is lower than that of the first alcohol.
[0064] The vapor pressure of the second alcohol is not particularly limited, but preferably the vapor pressure at room temperature, for example, 25° C. is 1 mPa or more, 2 mPa or more, 3 mPa or more, 4 mPa or more, 5 mPa or more, 6 mPa or more, 7 mPa or more, 8 mPa or more, 9 mPa or more, or 10 mPa or more. On the other hand, the vapor pressure of the second alcohol is not particularly limited, but preferably 100 Pa or less, 90 Pa or less, 80 Pa or less, 70 Pa or less, 60 Pa or less, 50 Pa or less, 40 Pa or less, or 30 Pa or less. By setting the vapor pressure of the first alcohol within a desired range, excellent storage stability and printability can be achieved.
[0065] Specifically, as the second alcohol, diols such as 2-ethyl-1,3-hexanediol (viscosity 323 mPa·s, boiling point 244°C, vapor pressure <1.4 Pa) and triols such as glycerol (viscosity 934 mPa·s, boiling point 290°C, vapor pressure 0.01 Pa) can be used. As the second alcohol, as long as the above-mentioned requirements for the second alcohol are met, one type can be used alone, or two or more types can be used in combination.
[0066] (Copper powder)
[0067] The copper powder is contained in the copper paste, and the paste is sintered to form a sintered body.
[0068] As copper powder, it is not particularly limited, and can be any of various commercial products, etc. As copper powder, it can be prepared using methods such as the high-pressure water atomization method described in International Publication No. 99 / 11407, the wet reduction precipitation method described in International Publication No. 2014 / 80662, etc. High-pressure water atomization is a method for preparing metal powder (such as copper) from molten metal, in which the vertical flow of the molten metal is passed through the center of the nozzle where the gas flows, and the molten metal is split by gas near the outlet of the nozzle, and then the molten metal after the split is further finely divided by the liquid ejected in an inverted cone. According to this method, by causing the splitting caused by gas and the splitting caused by liquid to act continuously on the molten metal, it is possible to industrially prepare metal powder (such as copper) with fine particle size, spherical or granular shape, and low oxygen content on a large scale and at low cost. In addition, the wet reduction precipitation method is a method for using an organic solvent having compatibility with water and reducing the surface tension of water as a solvent in the reduction of wet copper ions using a reducing agent such as hydrazine. Specifically, it is a method of using water and an organic solvent as a liquid medium, mixing a reaction solution containing monovalent or divalent copper ions with a reducing agent, and reducing the copper ions to generate copper particles. Generally speaking, particles larger than 0.7 μm can be prepared by high-pressure water atomization. The wet reduction precipitation method is suitable for preparing fine particles smaller than that.
[0069] In one embodiment, the average particle size of the copper powder (copper particles) is not particularly limited, and is preferably 0.05 μm or more, 0.06 μm or more, 0.07 μm or more, 0.08 μm or more, 0.09 μm or more, 0.1 μm or more, 0.12 μm or more, 0.15 μm or more, 0.17 μm or more, 0.2 μm or more, 0.22 μm or more, 0.25 μm or more, 0.27 μm or more, or 0.3 μm or more. On the other hand, the average particle size of the copper powder is preferably 2.0 μm or less, 1.9 μm or less, 1.8 μm or less, 1.7 μm or less, 1.6 μm or less, 1.5 μm or less, 1.4 μm or less, 1.3 μm or less, 1.2 μm or less, 1.1 μm or less, 1 μm or less, 0.9 μm or less, 0.8 μm or less, or 0.7 μm or less. By making the average particle size of the copper powder below the required value, the surface area of the copper powder is relatively increased, and it is easy to sinter at a low temperature. On the other hand, by making the average particle size of the copper powder above the required value, the increase in the price of the copper powder can be suppressed. In addition, by making the average particle size above the required value, it is possible to prevent a large number of particles from agglomerating and forming defects on the sintered body. It should be noted that in this specification, "average particle size" refers to the 50% particle size (D50), and more specifically, it is the central value of the particle size distribution measured using a laser particle size distribution meter or the like.
[0070] In one embodiment, the copper powder preferably includes a first copper particle having an average particle size of 50 nm or more and 900 nm or less, a second copper particle having an average particle size of 150 nm or more and 1 μm or less and an average particle size greater than 100 nm or more than the first copper particle, and a third copper particle having a plate-like, scaly, flat or flaky shape and an average particle size of 1.5 μm or more and 20 μm or less. By having a difference in average particle size of 100 nm or more between the first copper particle and the second copper particle, the first copper particle having a smaller average particle size fills the gap between the second copper particles having a larger average particle size, thereby obtaining a dense sintered body. In addition, by including a third copper particle in a flake shape or the like, cracks can be suppressed after applying and drying the paste.
[0071] The shape of the first copper particles is not particularly limited, and for example, a spherical shape, an ellipsoidal shape, a polyhedral shape, an irregular shape, a wire shape, a dendrite shape, or the like is preferred.
[0072] The average particle size of the first copper particles is preferably, for example, 60 nm or more, 70 nm or more, 80 nm or more, 90 nm or more, 100 nm or more, 120 nm or more, 150 nm or more, 170 nm or more, 200 nm or more, 220 nm or more, or 250 nm or more. On the other hand, the average particle size of the first copper particles is preferably 850 nm or less, 800 nm or less, 750 nm or less, 700 nm or less, 650 nm or less, 600 nm or less, 550 nm or less, 500 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, or 300 nm or less.
[0073] The content of the first copper particles is not particularly limited, and is preferably 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 45% by mass or more, 50% by mass or more, 55% by mass or more, 60% by mass or more, 65% by mass or more, or 70% by mass or more, relative to 100% by mass of the copper powder. On the other hand, the content of the first copper particles in the copper powder is preferably 90% by mass or less, 85% by mass or less, or 80% by mass or less, relative to 100% by mass of the copper powder.
[0074] The shape of the second copper particles is not particularly limited, and for example, a spherical shape, an ellipsoidal shape, a polyhedral shape, an irregular shape, a wire shape, a dendrite shape, or the like is preferred.
[0075] The average particle size of the second copper particles is preferably, for example, 160 nm or more, 170 nm or more, 180 nm or more, 190 nm or more, 200 nm or more, 220 nm or more, 250 nm or more, 270 nm or more, 300 nm or more, 320 nm or more, or 350 nm or more. On the other hand, the average particle size of the first copper particles is preferably 950 nm or less, 900 nm or less, 850 nm or less, 800 nm or less, 750 nm or less, 700 nm or less, 650 nm or less, 600 nm or less, 550 nm or less, 500 nm or less, 450 nm or less, or 400 nm or less.
[0076] The average particle size of the second copper particles is preferably 100 nm or more larger than the average particle size of the first copper particles. On the other hand, the average particle size of the second copper particles is preferably 900 nm or less, 800 nm or less, 700 nm or less, 600 nm or less, 500 nm or less, 400 nm or less, 300 nm or less, or 200 nm or less larger than the average particle size of the first copper particles.
[0077] The content of the second copper particles is not particularly limited, and is preferably 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 11% by mass or more, or 12% by mass or more, relative to 100% by mass of the copper powder. On the other hand, the content of the second copper particles in the copper powder is preferably 30% by mass or less, 27% by mass or less, 25% by mass or less, 22% by mass or less, 20% by mass or less, or 18% by mass or less, relative to 100% by mass of the copper powder.
[0078] The average particle size of the third copper particles is preferably, for example, 1.5 μm or more, 2 μm or more, 2.5 μm or more, 3 μm or more, 3.5 μm or more, 4 μm or more, 4.5 μm or more, 5 μm or more, 5.5 μm or more, or 6 μm or more. On the other hand, the average particle size of the third copper particles is preferably 20 μm or less, 19 μm or less, 18 μm or less, 17 μm or less, 16 μm or less, 15 μm or less, 14 μm or less, 13 μm or less, 12 μm or less, 11 μm or less, 10 μm or less, 9 μm or less, or 8 μm or less.
[0079] The content of the third copper particles in the copper powder is not particularly limited, and for example, it is preferably 5% by mass or more, 5.5% by mass or more, 6% by mass or more, 6.5% by mass or more, 7% by mass or more, 7.5% by mass or more, 8% by mass or more, 8.5% by mass or more, 9% by mass or more, or 9.5% by mass or more, relative to 100% by mass of the copper powder. On the other hand, the content of the third copper particles in the copper powder is preferably 60% by mass or less, 55% by mass or less, 50% by mass or less, 45% by mass or less, 40% by mass or less, 35% by mass or less, 30% by mass or less, 25% by mass or less, 20% by mass or less, 15% by mass or less, or 12% by mass or less, relative to 100% by mass of the copper powder.
[0080] A portion of the surface of the copper powder (copper particles) may be coated with an organic substance. As the organic substance, a compound of a polysaccharide or a fatty acid is preferably used. When the polysaccharide molecule is coated with the copper powder, the outer side (the side in contact with the solvent) becomes hydrophilic, and thus interacts with the hydroxyl group of the organic solvent in the copper paste to bring about a moderate viscosity. On the other hand, the carboxyl group of the fatty acid is bonded to the surface of the copper particle, and the end on the opposite side of the fatty acid becomes hydrophobic, thereby being able to improve the dispersibility of the copper particles and inhibit the aggregation of the particles. Since the polysaccharide and the fatty acid have these effects, as a result, the copper paste can be spread over the entire interface with a uniform layer thickness, and the bonding strength can be excellent.
[0081] As polysaccharides, specifically, for example, one or more selected from gum arabic, carboxymethyl cellulose, hydroxyethyl cellulose, cellulose nanofibers, starch, glycogen, agarose (agar), pectin and alginic acid, and their salts can be used, but not limited to these, sulfur-containing polysaccharides such as carrageenan can be used. Among them, it is preferred to use one or more selected from gum arabic and sodium alginate.
[0082] As the fatty acid, for example, medium-chain fatty acids such as valeric acid, octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, and tetradecanoic acid can be used. Among them, it is preferred to use one or more selected from octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, and tetradecanoic acid.
[0083] The surface coverage rate of the organic matter is not particularly limited, but it is preferred to coat the copper powder with a carbon content of 0.05% to 0.8%, preferably 0.1% to 0.5%, and an oxygen content of 0.05% to 1.5%, preferably 0.1% to 1%, relative to 100% by mass of the copper powder having the coating layer. In this way, by making the carbon content or the oxygen content greater than the required amount, the hydrophilicity caused by the polysaccharide molecules on the surface of the copper powder can be fully expressed, the viscosity of the copper paste is reduced to form a uniform paste layer, and the bonding strength of the obtained sintered body is excellent. On the other hand, by making the carbon content and the oxygen content less than the required amount, for example, when firing in a nitrogen atmosphere, it is possible to prevent carbon-containing and oxygen-containing components from remaining inside the sintered body, and it is possible to make the thermal conductivity and bonding strength excellent.
[0084] When the copper powder is used as the copper powder, the first copper particle, the second copper particle and the third copper particle, at least a portion of the surface of at least one of the first copper particle and the second copper particle is preferably coated with an organic substance. As the organic substance, polysaccharides and fatty acids can be used, but polysaccharides are preferably used. In addition, for the third copper particle, at least a portion of the surface can also be coated with an organic substance (polysaccharides, fatty acids, etc.).
[0085] In the copper paste involved in the present embodiment, the total content of elements other than copper in the copper powder is not particularly limited, and is preferably, for example, less than 1 mass%, less than 0.5 mass%, or less than 0.1 mass% relative to 100 mass% of the copper powder. Among the components other than copper, especially metal elements, due to segregation on the surface of the copper powder or formation of oxides, it is possible to deteriorate the sintering properties, and to be dissolved in the copper powder, so as to reduce the conductivity of the sintered body. If the total content of metal elements such as As, Co, Cr, Fe, Ir, P, S, Sb, Se, Te, Ti, V, and Zr is less than the required amount, the resistivity of the copper paste sintered body can be made lower, and more excellent thermal conductivity can be shown. With such a thermal conductivity, for example, the heat generated by the power module can be efficiently dissipated to the outside.
[0086] (Other ingredients)
[0087] The copper paste according to the present embodiment may contain, in addition to the above-mentioned components, a dispersant or surfactant composed of amines, an antioxidant, a reducing agent such as hydrazine, glass frit, a binder represented by a resin component, and the like.
[0088] The resin component is not particularly limited, and for example, one or more selected from cellulose resins such as methyl cellulose, ethyl cellulose, and carboxymethyl cellulose, acrylic resins, butyral resins, alkyd resins, epoxy resins, and phenolic resins can be used.
[0089] As the content of the resin component, there is no particular limitation, and relative to 100 mass % of copper powder, it is preferably more than 0 mass %, more than 0.01 mass %, more than 0.05 mass %, and more than 0.1 mass %. As the content of the resin component, relative to 100 mass % of the mass of the copper particles, it can be less than 10 mass %, less than 9 mass %, less than 8 mass %, less than 7 mass %, less than 6 mass %, less than 5 mass %, less than 4 mass %, less than 3 mass %, less than 2 mass %, less than 1 mass %, less than 0.5 mass %, less than 0.1 mass %, less than 0.05 mass %, and less than 0.01 mass %, preferably without copper powder. If the copper paste contains a resin component, the sintering property (especially below 350° C.) sometimes deteriorates. For example, a thermosetting resin such as an epoxy resin also remains in the copper paste sintered body after sintering. When using cellulose resins, although thermal decomposition begins at around 300°C, heating at a temperature of 400°C or higher is required for complete thermal decomposition, and sintering in an oxygen atmosphere is required to remove carbon residues generated by thermal decomposition, and the copper powder may be oxidized. If the copper paste does not contain a resin component, sintering can be performed in a non-oxidizing atmosphere and at a relatively low temperature, so a high-density copper sintered body can be formed without causing a decrease in conductivity due to oxidation of the copper powder. In the copper paste involved in this embodiment, since the second alcohol with high viscosity is included, the viscosity can be adjusted to an appropriate value even if a resin component is not included.
[0090] The copper paste preferably contains no epoxy group-containing silane coupling agent and an amino group-containing silane coupling agent, or contains the epoxy group-containing silane coupling agent and the amino group-containing silane coupling agent in a total amount of more than 0 mass % and 0.05 mass % or less relative to 100 mass % of the copper powder.
[0091] (Use of copper paste)
[0092] The copper paste involved in the present embodiment has high electrical conductivity and thermal conductivity as described above, and has excellent storage stability and processability. In addition, the copper paste involved in the present embodiment can be fired at low temperature and in a short time, and can show high chip shear strength. Therefore, it can be used for the purpose of wiring formation in electronic components such as power modules, chip resistors, chip capacitors, solar cells, printed wiring substrates, and electronic installations such as substrates with through holes. For example, the copper paste involved in the present embodiment is applied on power modules, substrates for carrying solar cells or electronic installations, printed wiring substrates, substrates with through holes, etc., and a copper sintered body can be formed by sintering. Here, as a substrate material, for example, a silicon substrate, a silicate glass, alumina, quartz and other oxide substrates, silicon nitride, aluminum nitride and other nitride substrates, silicon carbide, titanium carbide and other carbide substrates, polyimide, polyethylene terephthalate, polyethylene naphthalate and other resin substrates, and a substrate with a transparent conductive film (TCO) or a metal film on the surface can be used.
[0093] (Preparation of copper paste)
[0094] The copper paste involved in the present embodiment can be prepared by mixing the above copper powder with a solvent and kneading it using a planetary mixer or other device as needed. In addition, a three-roll mill can also be used to improve the dispersibility of the copper powder as needed. In addition, the paste can also be applied to a filter or deaerated.
[0095] (Firing of copper paste)
[0096] In the case of firing the copper paste involved in this embodiment, there are no special restrictions on the method and conditions, and it can be carried out in any way according to the target product and the object material of the paste coating. However, it is preferred to dry and remove the first alcohol before firing the copper paste involved in this embodiment. Thus, since the presence ratio of the second alcohol around the copper powder during firing is increased, the oxidation of the copper powder during firing can be more effectively prevented. As drying conditions, there are no special restrictions, and it can be arbitrarily set according to the boiling point of the first alcohol and the target product, for example, preferably at 50-200°C in an atmospheric atmosphere, particularly preferably at 60-150°C, and heated for 1-60 minutes. It is also possible to dry under reduced pressure to further reduce the heating temperature. It is also possible to heat and dry under an inert gas atmosphere or a reducing atmosphere.
[0097] The copper paste involved in this embodiment can be fired at a low temperature and in a short time, so the firing conditions are not particularly limited. For example, in an inert gas atmosphere such as nitrogen or argon, or in a reducing atmosphere containing about 0.1-30% by volume of hydrogen, ammonia, carbon monoxide, alcohol vapor, etc., sintering is performed at 150-400°C or 200-350°C, especially 250-300°C for 10 seconds to 60 minutes, especially 2-30 minutes, thereby obtaining a sintered body with excellent electrical conductivity, thermal conductivity and chip shear strength.
[0098] Example
[0099] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0100] [Evaluation of physical properties and performance of samples]
[0101] The physical properties and performance of the pastes prepared under the compositions and conditions described below were evaluated according to the following evaluation methods.
[0102] (Determination of viscosity, and determination of Casson yield stress and Casson viscosity)
[0103] The viscosity of the prepared paste was measured using a dynamic viscoelasticity measuring device equipped with a cone-plate type spindle (RST cone-plate Rheometer manufactured by Brookfield) at a shear rate of 10 s. -1 The viscosity of the copper paste under 10 In addition, the square root of the shear stress (σ) (√
[0104] The Casson curve is a graph with the vertical axis being the square root (√γ) of the shear rate (γ) and the horizontal axis being the shear rate (γ). When an approximate straight line is obtained in the graph, the Casson curve can be drawn. -1 The intercept of the approximate straight line with the vertical axis in the above region is the square root of the Casson yield stress (√σ0), and the slope of the approximate straight line is the square root of the Casson viscosity (√η ∞ Here, obtaining an approximate straight line means R 2 When the value (coefficient of determination) is 0.9 or more.
[0105] As a representative result, a Casson graph was prepared for three types of copper pastes (Comparative Example 2, Comparative Example 1, and Example 4, details of which will be described later). Figure 1 This is Comparative Example 2 (η 10 =185Pa·s) of the paste. The shear rate is 10s -1 R in the above area2 The value is 0.0615, Figure 1 It can be seen that since it is not linear, it cannot be fitted by the Casson formula.
[0106] on the other hand, Figure 2 is Comparative Example 1 (η 10 =11Pa·s) of the paste. In addition, Figure 3 Example 4 (η 10 =8Pa·s) paste Casson curve. Figure 2 and Figure 3 In the Casson curve shown, the shear rate is 10s -1 R in the above area 2 The values are 0.9994 and 0.9996 respectively, and the data can be approximated by a straight line. In either case, a sharp increase in √σ in the slow shear rate region and a slow increase in √σ in the fast shear rate region can be seen. Since the sharp increase corresponds to the phenomenon of crushing the agglomerates of the fine powder contained in the paste, as a result reflecting the characteristics of the homogeneous paste, the fast shear rate (10s -1 The approximate straight line in the above area obtains the intercept: √σ0 and the slope: √η ∞ .
[0107] (Observation of tissue defects)
[0108] The prepared paste was applied to a glass substrate by stencil printing using a metal mask so that the paste had a square shape of 20 mm on a side, and then dried in air at 100° C. for 5 minutes. The structure of the dried paste surface was observed using a stereoscopic optical microscope at a magnification of 10 times to examine the presence of structural defects such as holes, protrusions, and cracks.
[0109] The specific examples are shown below for explanation. The pastes of Comparative Example 1 and Example 4, which can be approximated as straight lines in the Casson curve graph, were printed on a glass substrate and dried, and the surface of the obtained dried products was observed. The results are shown below. Figure 4 This is an optical microscope photograph of the dried product of the paste of Comparative Example 1. Figure 5 : is an optical microscope photograph of the dried product of the paste of Example 4. In the dried product of the paste of Comparative Example 1, a plurality of pores ( Figure 4 On the other hand, no holes or other structural defects were observed in the dried product of the paste of Example 4. The same test was performed on the pastes prepared under various process conditions to confirm the presence or absence of surface defects and printing defects.
[0110] (Determination of resistivity)
[0111] Using a metal mask, the prepared paste is applied to a glass substrate by stencil printing so that the paste becomes a square with a side length of 20 mm, and then dried in the atmosphere at 100°C for 5 minutes. Then, in a nitrogen atmosphere, a high-temperature press is used to apply a load of 20 MPa while pressurizing and sintering at a heating temperature of 280°C and a heating time of 2 minutes to obtain a copper paste sintered body with a thickness of about 20 μm. For the sintered body, the resistivity is measured using a DC 4-probe resistance measuring device with the probe spacing set to 1 mm. If the resistivity is converted into thermal conductivity according to the Wiedemann-Franz law, it corresponds to 134 Wm -1 K -1 above.
[0112] (Determination of chip shear strength)
[0113] A copper plate with a thickness of 1 mm was used as a substrate, and a copper paste was applied thereon to a thickness of 100 μm. A semiconductor chip with a size of 2 mm × 2 mm × 0.4 mm and made of silicon carbide (SiC) was then placed thereon. A 500 nm thick Ti layer and a 500 nm thick Cu layer were formed on the surface of the SiC chip in contact with the copper paste using a sputtering method. For the laminate thus obtained, a high temperature press was used in a nitrogen atmosphere with a load of 20 MPa, the firing temperature was set to 280°C, and pressure sintering was performed for 3 minutes. In the sample cooled to room temperature, the adhesion strength between the SiC chip and the copper substrate was measured as the chip shear strength using a chip shear tester (DAGE4000 manufactured by Nordson).
[0114] (Evaluation Criteria)
[0115] For these measurement results, the case where all four conditions of (1) the dried paste has no surface defects, (2) the dried paste has no printing defects, (3) the resistivity of the sintered body is 5 μΩcm or less, and (4) the die shear strength of the sintered body is 30 MPa or more was evaluated as judgment AA. The case where three conditions were met was A, the case where two conditions were met was B, and the case where one condition was met or none of the conditions were met was C.
[0116] [Test 1: Effect of paste viscosity and Casson yield stress]
[0117] (Example 1)
[0118] The copper particles used were first spherical copper particles with a D50 of 270 nm, second spherical copper particles with a D50 of 380 nm, and third flake-shaped copper particles with a D50 of 7 μm. The two types of copper particles other than flake-shaped particles were copper particles whose surfaces were coated with polysaccharide gum arabic.
[0119] First, the first copper particle: the second copper particle: the third copper particle were mixed in a mass ratio of 65:30:5. The impurities contained in the first to third copper particles were 0.3% carbon, 0.7% oxygen, and 0.2% metal elements other than copper. Ethylene glycol as the first alcohol and glycerol as the second alcohol were prepared, and weighed in a mass ratio of 60:20:20 copper particles: ethylene glycol: glycerol, and kneaded with a planetary mixer to prepare a copper paste. The evaluation results are shown in Table 1.
[0120] (Examples 2-7 and Comparative Examples 1-4)
[0121] A copper paste was prepared under the same conditions as in Example 1 except that the mass ratio of the copper powder to the solvent and the mass ratio of the first to third copper particles were changed. The evaluation results are shown in Table 1. The value "N / A" in Table 1 indicates that a good approximate straight line (fit) was not obtained in the Casson curve diagram.
[0122] [Table 1]
[0123]
[0124] It is known that by using the first alcohol (ethylene glycol) having a viscosity in the range of 3 mPa·s to 70 mPa·s and the second alcohol (glycerol) having a viscosity in the range of 300 mPa·s to 1000 mPa·s as solvents and adjusting the paste composition, η can be controlled. 10 ,√σ0,√η ∞ In addition, it can be seen that by adjusting η 10 and √σ0, a well-evaluated paste can be obtained.
[0125] [Test 2: Influence of the Type of First Alcohol]
[0126] (Examples 8-13 and Comparative Examples 5-7)
[0127] Pastes were prepared and evaluated in the same manner as in Example 3 except that ethylene glycol as the first alcohol was changed to an alcohol shown in Table 2. Table 2 shows the evaluation results.
[0128] [Table 2]
[0129]
[0130] As can be seen from Table 2, the first alcohol is not limited to ethylene glycol, and a sintered body having desired properties can be obtained as long as a copper paste having a monovalent or divalent alcohol with a viscosity within a desired viscosity range is used.
[0131] [Test 3: Influence of the Type of Second Alcohol]
[0132] (Example 14, Comparative Examples 8-9)
[0133] Pastes were prepared and evaluated in the same manner as in Example 3 except that glycerin as the second alcohol was changed to an alcohol shown in Table 3. Table 3 shows the evaluation results.
[0134] [Table 3]
[0135]
[0136] As can be seen from Table 3, the second alcohol is not limited to ethylene glycol, and a sintered body having desired properties can be obtained as long as a copper paste using a diol or triol having a viscosity within a desired viscosity range is used.
Claims
1. A copper paste, characterized in that It contains copper powder and alcohol solvent, The alcohol solvent comprises a first alcohol and a second alcohol, The first alcohol is one or more selected from monohydric alcohols and dihydric alcohols having a viscosity of 3 mPa·s or more and 70 mPa·s or less at 25° C., The second alcohol is one or more selected from diols and triols having a viscosity of 300 mPa·s or more and 1000 mPa·s or less at 25° C., The copper paste is heated at 25°C and a shear rate of 10 s -1 Viscosity η 10 is 1Pa·s or more and 50Pa·s or less, The square root of the Casson yield stress σ0√σ0 is 10Pa 1 / 2 the following.
2. The copper paste according to claim 1, wherein Casson viscosity η ∞ The square root of √η ∞ 1 (Pa·s) 1 / 2 the following.
3. The copper paste according to claim 1 or 2, wherein The copper powder includes first copper particles, second copper particles and third copper particles. The average particle size of the first copper particles is greater than or equal to 50 nm and less than or equal to 900 nm. The second copper particles have an average particle size of 150 nm or more and 1 μm or less, and are larger than the first copper particles by 100 nm or more. The third copper particles are plate-shaped, scale-shaped, flat, or flake-shaped, and have an average particle size of 1.5 μm to 20 μm.
4. The copper paste according to claim 3, wherein The copper powder includes 1% by mass or more and 30% by mass or less of the second copper particles and 5% by mass or more and 60% by mass or less of the third copper particles relative to 100% by mass of the copper powder.
5. The copper paste according to claim 1 or 2, wherein The total amount of the first alcohol and the second alcohol is 5% by mass or more and 50% by mass or less relative to 100% by mass of the total amount of the copper powder, the first alcohol and the second alcohol.
6. The copper paste according to claim 1 or 2, wherein: The copper paste does not contain a resin, or contains more than 0 mass % and 10 mass % or less of the resin relative to 100 mass % of the copper powder.
7. The copper paste according to claim 1 or 2, wherein: The copper paste does not contain a silane coupling agent having an epoxy group and a silane coupling agent having an amino group, or contains more than 0 mass % and 0.05 mass % or less of the silane coupling agent having an epoxy group and the silane coupling agent having an amino group in a total amount relative to 100 mass % of the copper powder.
8. The copper paste according to claim 1 or 2, wherein The first alcohol includes at least one selected from 1-hexanol, 1-heptanol, 2-heptanol, 1-octanol, 2-octanol, 2-ethyl-1-hexanol, benzyl alcohol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, and 2,3-butylene glycol.
9. The copper paste according to claim 3, wherein: At least one of the first copper particle and the second copper particle is covered with a polysaccharide on at least a portion of its surface.
10. The copper paste according to claim 3, wherein At least one of the first copper particle and the second copper particle includes one or more selected from octanoic acid, nonanoic acid, decanoic acid, dodecanoic acid, and tetradecanoic acid in at least a portion of the surface.
Citation Information
Patent Citations
Method of producing metal powder by atomizing and apparatus therefor
WO1999011407A1
Copper powder and method for producing same
WO2014080662A1